Ridge preservation of a novel extraction socket applying Bio-Oss® collagen: An experimental study in dogs - Qihang Fan; Hao Zeng; Wei Fan; Tao Wu; Jing Sun; Qi Yan; Bin Shi (Elsevier, 2021)
Background: Bio-Oss® collagen (BC) has been used in clinical applications for years but the ridge preservation property of BC remains controversial. There is no animal model accurately simulates the extraction socket in people. The aim of this study was to assess the ridge preservation of a novel extraction sockets with a thin buccal plate using BC. Materials and methods: Two beagle dogs were used to assess the characterization of the novel extraction socket. The width and height of the socket were measured and biopsies of the socket were collected for histologic examination. Four beagle dogs were used to assess the ridge preservation property of BC. BC was placed in the socket and socket left untreated was set as control group (CT). Cone-beam computed tomography analysis, histological examination, and micro-CT analysis were used to evaluate the ridge preservation. Results: The novel extraction socket had obvious larger volume with a markedly narrow buccal wall than mandible extraction sockets. At 12 weeks, the width of the crest of the alveolar ridge preservation ratios was 34% for the CT and 82% for the BC. BC group had larger socket volume compare to CT group. BC group had a significant higher bone density in the middle and apical areas of the alveolar bone. Socket placed with BC showed significantly less vertical bone loss compared with CT group. Conclusion: Extraction site with a significantly larger dimension and a very thin buccal plate was established. Extraction sockets filled with BC exhibit excellent maintenance of alveolar bone volume.